Solving the Economic Dispatch Problem using Tabu Search - Kamsawang, Suwit; Boonseng, Jongrak; Pothiya, Sarawut (Engineering and Applied Science Research, 2013)
This paper presents an efficient approach for solving the economic dispatch problem (EDP) using Tabu Search Algorithm (TSA). Nowadays the TSA is the most popular meta-heuristic technique for optimization because it has the ability to escape local optima by using a short-term memory of recent solutions lead to global optima. In this paper considered three case studies and compared with genetic algorithm (GA) (ธวัช เกิดชื่น และคณะฯ, 2540) and Excel Solver (ES) (วรวัฒน์ เสงี่ยมวิบูล, 2544). The programming for simulation by MATLAB. The results shown solving the EDP using TSA yield solutions better than GA and ES and easier to implementation